Impact of Training on the Performance of Employees in the Commercial Banks of Nepal - Palikhe, Amin; Thapa, Sarala (Journal of Nepalese Business Studies, 2023)
Enhancing employee performance requires the deliberate use of training and development. Whether commercial banks used the training program and analyzed their impact is the question being raised in the acaemic community. Therefore, this study aims to evaluate the impact of training on the employee’s performance in commercial banks in Nepal. Two commercial banks in Pokhara valley namely Nabil Bank and NMB Bank were selected randomly, as a descriptive cum causal research design, which covered 89 respondents as a convenient sample. Primary sources and a questionnaire survey have been used to collect the data. The statistical software SPSS 17 version has been carried out to analysis the relationships and impacts of dependent and independent variables. The study shows that the existence of training programs in the commercial bank of Nepal is important. The findings show that an employee's level of performance is increased as they receive more training and operating training regularly. There was a significant positive impact of employee training on their performance in commercial banks. As a result, it is advised that commercial banks as a whole receive well-planned, organized, and coordinated training programs. Since they serve as a crucial strategic link between the company's goal and day-to-day operations, the organization should put its best effort into developing training policies and practices. Further, it could be useful to study other banks and financial institutions regarding the impact of training on the employees’ performance of any bank and institution in the future by using other variables.